Some Insights into Translating and Teaching English for Specific Purposes - Sierocka, Halina (HERMES - Journal of Language and Communication in Business, 2024)
This short paper aims to highlight and concisely explore – but not address in depth -some aspects related to translating and teaching English for specific purposes (mainly English for Legal Purposes) The following questions will be briefly considered: What is the impact of comparative law on legal translation? How can tricky terms in legal translation be taught effectively? How can mediation activities and student self-reflection be utilised to train legal skills? How can teaching plain English to PhD students improve their writing in a scientific context? The paper starts with a brief introduction to the concept of language and communication for specific purposes, with a particular emphasis put on English for Legal Purposes. The second section of the essay refers to issues connected with legal translation; its specificity and the role of comparative law in the quality of translation and interpretation. The third and last part of the paper is dedicated to the issue of instructing languages for specific purposes. It mainly tackles the problem of equipping students with such linguistic competencies, skills, and knowledge which are most valuable for their study and work.